(untitled) (World Bulletin of Public Health, 2022)
Urolithiasis is one of the most common pathologies among urological diseases and occurs in at least 1-3% of the population, most often in people of working age - 20-50 years. Urolithiasis is recorded in 10% of the population and has an annual increase.